Functional Rescue of F508del-CFTR Using Small Molecule Correctors - Molinski, Steven; Eckford, Paul D.; Pasyk, Stan; Ahmadi, Saumel; Chin, Stephanie; Bear, Christine E. (Frontiers in Pharmacology, 2012)
High-throughput screens for small molecules that are effective in “correcting” the functional expression of F508del-CFTR have yielded several promising hits. Two such compounds are currently in clinical trial. Despite this success, it is clear that further advances will be required in order to restore 50% or greater of wild-type CFTR function to the airways of patients harbouring the F508del-CFTR protein. Progress will be enhanced by our better understanding of the molecular and cellular defects caused by the F508del-mutation, present in 90% of CF patients. The goal of this chapter is to review the current understanding of defects caused by F508del in the CFTR protein and in CFTR-mediated interactions important for its biosynthesis, trafficking, channel function and stability at the cell surface. Finally, we will discuss the gaps in our knowledge regarding the mechanism of action of existing correctors, the unmet need to discover compounds which restore proper CFTR structure and function in CF affected tissues and new strategies for therapy development.